Dietary intake and stunting in children aged 6-23 months in rural Sumba, Indonesia - Suryadi Limardi; Dini Mutia Hasanah; Ni Made Dwiyathi Utami (Paediatrica Indonesiana, 2022)
Background Linear growth retardation in the first two years of life leads to numerous harmful consequences. Lack of diversity in the diet and inadequate amounts of complementary food have been associated with stunted growth in children. Objective To assess the dietary intake and investigate for associations with stunting among children aged 6-23 months. Methods This case-control study compared the dietary intake of children aged 6-23 months with and without stunting in the South and West Wewewa subdistricts of Southwest Sumba, East Nusa Tenggara, Indonesia. Complementary food types, dietary diversity, and nutritional intake were assessed and compared between groups. Nutrient intake sufficiency and stunting were analyzed by logistic regression. Results A total of 200 participants were equally allocated into groups with and without stunting. Only 6% of stunted children received adequate complementary food diversity compared to 14% of non-stunted children (P=0.05). The stunted group had significantly lower consumption of flesh foods (beef, fish, poultry, organ meat, and other kinds of meat) compared to the non-stunted group (7% vs. 16% of subjects, respectively; P<0.05). The median total protein intake was also significantly lower in stunted children compared to non-stunted children [7.72 (IQR 6.46, 11.31) g vs. 10.02 (IQR 6.53, 13.95) g, respectively; P<0.05] although no association was found between protein intake sufficiency and stunting in the multivariate analysis. Only maternal unemployment was positively associated with stunting (OR 2.32; 95%CI 1.26 to 4.26). Conclusion Overall, most subjects did not receive sufficient amounts of nutrients. Although dietary diversity was not found to be significantly different between those with and without stunting, a significantly lower proportion of stunted children consumed flesh food. The stunted group also received significantly lower protein from their diet although no association was found between nutrient intake sufficiency and stunting. Further studies are needed to longitudinally assess the effects of macronutrient and micronutrient intake sufficiency on linear growth in children.